Study guides

☆☆

Q: 9 minus 2x equals 35

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

if 9 - 2x = 35 then 9-2x-9 =35-9 -2x = 26 we want make 'x' subject of this equation then we divide both sides by -2 -2x/-2 = 26/-2 x = -13

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

x = 9

6 2(6) + 3 = 9

3x2 + 2x + 2 = 0 Can not be factored. You can however solve it for x: 3x2 + 2x = -2 x2 + 2x/3 = -2/3 x2 + 2x/3 + 1/9 = -2/3 + 1/9 (x + 1/9)2 = -5/9 x + 1/9 = ±√(-5/9) x = -1/9 ± i√(5/9) x = -1/9 ± i√5 / 3 x = -1/9 ± 3i√5 / 9 x = (-1 ± 3i√5) / 9

Related questions

if 9 - 2x = 35 then 9-2x-9 =35-9 -2x = 26 we want make 'x' subject of this equation then we divide both sides by -2 -2x/-2 = 26/-2 x = -13

-2x+9y=-35 add 2x to both sides to get 9y=2x-35 divide both sides by 9 to get y=2/9 x - 35/9 the Y intercept is 0, ~-3.889 and the slope is 2/9

35

9 - - 6 + 20 = 35

6 - x + 7 - 3x - 5 = -2x - 10 ∴ x + 3x - 2x = 6 + 7 - 5 + 10 ∴ 2x = 18 ∴ x = 9

(2x - 9)(2x +9)

It is a quadratic equation and its solutions are: x = -3/2 and x = 3

Let 6x - 2x - 9 = a, where a is an arbitrary constant. Then 4x - 9 = a 4x = a+9 x = (a+9)/4

9 Please tell me you're in 4th grade.

It is an algebraic expression involving x. Of do you mean 'what is x if 2x - 9 equals 9?' 2x - 9 = 9 ⇒ 2x - 9 + 9 = 9 + 9 ⇒ 2x = 18 ⇒ 2x ÷ 2 = 18 ÷ 2 ⇒ x = 9

(2x - 9)(2x - 9) or (2x - 9)2

(2x - 9)(2x - 9) or (2x - 9)2

People also asked